Sleep Disordered Breathing in Children with Mitochondrial Disease - Mosquera, Ricardo A. (Pulm Med, 2014)
A retrospective chart review study was performed to determine the presence of sleep disordered breathing (SDB) in children with primary mitochondrial disease (MD). The symptoms, sleep-related breathing, and movement abnormalities are described for 18 subjects (ages 1.5 to 18 years, 61% male) with MD who underwent polysomnography in our pediatric sleep center from 2007 to 2012. Of the 18 subjects with MD, the common indications for polysomnography were excessive somnolence or fatigue (61%, N = 11), snoring (44%, N = 8), and sleep movement complaints (17%, N = 3). Polysomnographic measurements showed SDB in 56% (N = 10) (obstructive sleep apnea in 60% (N = 6), hypoxemia in 40% (N = 4), and sleep hypoventilation in 20% (N = 2)). There was a significant association between decreased muscle tone and SDB (P: 0.043) as well as obese and overweight status with SDB (P = 0.036). SDB is common in subjects with MD. Early detection of SDB, utilizing polysomnography, should be considered to assist in identification of MD patients who may benefit from sleep-related interventions.